European visa cooperation: interest politics and regional imagined communities - Mogens Hobolth (London School of Economics and Political Science (LSE), European Institute, 2011)
Since the early 1990s the European Union has struggled to increase integration in the sovereignty sensitive areas of justice and home affairs and foreign policy. The aim of this paper is to enhance our understanding of what patterns of cooperation have been established between the member states, and why. I do so by analysing the case of short-stay visa policy. Visas are a corner stone of EU's border control, regulating access to the Union's area of freedom, security and justice. It is moreover an instrument used in foreign and diplomatic relations. As a field where the member states' cooperation is particularly intense it is an 'extreme case' well-suited for drawing out empirical patterns and developing theoretical concepts. The paper is based on a network analytical approach and a new dataset of all the EU/Schengen member states' mutual consular visa assistance agreements. This I use to document the extent and pattern of cooperation from 2005 to 2010. I show that the member states rely intensively on each other's consular services. They mainly share sovereignty in four distinct regional clusters – a Nordic, Benelux, Southern European and an emerging Central Eastern. France and Germany are at the centre of the network. To explain this structure of cooperation I discuss the relative merits of realist, liberal intergovernmentalist and constructivist approaches. I show how they each identify important dynamics but emphasise the relative merits of a constructivist perspective. I put forward a new concept of 'regional imagined communities' which explains cooperation by the existence of shared identities owing to regional commonalities in language and state-building histories. I argue that the concept improves our understanding of European integration in visa policy, and suggest it might hold wider potential for explaining dynamics of collaboration in other sovereignty sensitive policy areas.
Keywords: 330; Regional imagined communities; Intensive transgovernmentalism; Sovereignty; Justice and home affairs; European foreign policy; Schengen; Visa; Consular cooperation